Positron emission tomography shows that impaired frontal lobe functioning in Parkinson’s disease is related to dopaminergic hypofunction in the caudate nucleus - Brück, Anna; Portin, Raija; Lindell, Arja; Laihinen, Arto; Bergman, Jörgen; Haaparanta, Merja; Solin, Olof; Rinne, Juha O (Neuroscience letters, 2001)
We examined the relation between the dopaminergic function and the cognitive performance of patients with Parkinson's disease (PD). The subject sample consisted of ten patients in the early course of PD and with no previous antiparkinsonian medication. The dopaminergic function of the caudate nucleus and the putamen was studied with [ 18F]fluorodopa positron emission tomography, and the cognitive performance with a comprehensive battery of neuropsychological tests including tests sensitive to frontal lobe function. The decreased [ 18F]fluorodopa uptake in the right caudate nucleus was found to be related to slow processing time, measured as the difference between the incongruent and the congruent subtests of the Stroop Test ( r=−0.85, P=0.002), a similar trend was seen in the left caudate ( r=−0.60, P=0.07). Similar correlation was not detected in the putamen. The present findings provide evidence that the decreased dopaminergic function in the right caudate nucleus is related to the impaired performance in tests sensitive to frontal lobe function in patients at an early stage of PD and with no antiparkinsonian medication.